2020
DOI: 10.1096/fj.202000925r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitinase‐3‐like protein 1 on glucose metabolism: In vitro skeletal muscle and human genetic association study

Abstract: We investigated the effect of chitinase‐3‐like protein 1 (CHI3L1) on glucose metabolism and its underlying mechanisms in skeletal muscle cells, and evaluated whether the observed effects are relevant in humans. CHI3L1 was associated with increased glucose uptake in skeletal muscles in an AMP‐activated protein kinase (AMPK)‐dependent manner, and with increased intracellular calcium levels via PAR2. The improvement in glucose metabolism observed in an intraperitoneal glucose tolerance test on male C57BL/6J mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Moreover, activated RhoA interacts with ROCK, promoting its activation. ROCK phosphorylates various substrates, including myosin light chain (MLC) and LIM kinase (LIMK), which results in cytoskeletal reorganization and the modulation of cell motility and adhesion [ 29 ]. This can contribute to immune cell recruitment and tissue inflammation.…”
Section: Relevant Sections and Discussionmentioning
confidence: 99%
“…Moreover, activated RhoA interacts with ROCK, promoting its activation. ROCK phosphorylates various substrates, including myosin light chain (MLC) and LIM kinase (LIMK), which results in cytoskeletal reorganization and the modulation of cell motility and adhesion [ 29 ]. This can contribute to immune cell recruitment and tissue inflammation.…”
Section: Relevant Sections and Discussionmentioning
confidence: 99%
“…CHI3L1 has high binding affinity for chitin and chitin oligosaccharides. It plays a role in numerous biological and pathological processes, including extracellular matrix formation, cell proliferation and differentiation, migration, chemotaxis, angiogenesis, inflammation, endothelial dysfunction, and tissue remodeling [ signaling pathways downstream of CHI3L1, including the mitogen-activated protein kinase pathway, the phosphoinositide 3-kinase/protein kinase B pathway, the c-Jun N-terminal kinase/caspase-3 pathway, and the cytokine signaling such as interleukin 1beta [28][29][30][31]. Over the recent decades, a number of studies have demonstrated that CHI3L1 is associated with asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to what we have summarized above, with the development of biotechnology, more and more myokines have been discovered, such as Apelin ( 116 ), Chitinase-3-like protein ( 117 ), Follistatin-like 1 ( 118 ), Dipeptidyl Peptidase IV ( 119 ), MG53 ( 120 ) and METRNL ( 121 ), which they also play a key role in maintaining the human homeostasis of the body. Further studies are needed to determine whether they are related to DN and, if so, how Table 1 .…”
Section: Myokines and Dnmentioning
confidence: 99%